TERRA SIGILLATA DECORATA A MATRICE DI MEDIA ETÀ IMPERIALE DA VERONA: NUOVI DATI SULLE PRODUZIONI NORD-ITALICHE - Mantovani, Valentina; Stuani, Roby (Rei Cretariae Romanae Fautorum Acta, 2022)
The present study derives from the presence in the excavation at the Episcopal Seminary of Verona (Italy) of an interesting group of mould-made terra sigillata of mid-imperial date, which has no close parallels in the Gallic, Pannonian or Oriental productions. The aim is to place this material in its historical context and to identify its source. The strong similarities between this body of material and some contemporary terra sigillata products found in northern Italy (some of which have been attributed through chemical analysis to a northern Adriatic production) has enabled the attributions of the cups from the Seminary to one or more sources in the Po Valley region.